The Impact Of The Development Of The Culture Of The Turan Peoples On World Civilization (Zien Journal of Social Sciences and Humanities, 2025)
This article describes the transformation of the culture of the ancient Turanian peoples into world civilization, as well as the scholars who made a significant contribution to the development of Islam in Central Asia